2017
DOI: 10.1515/ama-2017-0046
|View full text |Cite
|
Sign up to set email alerts
|

Transient Analysis of a Railgun with Permanent Magnets Support

Abstract: Abstract:The calculation and measurement results of transients for an electrodynamic accelerator with permanent magnet support have been presented in this paper. The calculations have been made using the magnetostatic model in the Maxwell software, as well as using a Matlab/Simulink transient model. The waves of mechanical parameters (projectile velocity and acceleration, force) and electric ones (excitation current and capacitor voltage) have been analyzed for different supply conditions (voltage value, capac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…di y dt = 1 L dy y, i y u y − R y i y − e vy y, i y dy dt (18) where u x and u y are the supply voltages for the xand y-axis, respectively, and R x and R y indicate the resistance of the control windings for the xand y-axis, respectively. where ux and uy are the supply voltages for the x-and y-axis, respectively, and Rx and Ry indicate the resistance of the control windings for the x-and y-axis, respectively.…”
Section: Transient Time Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…di y dt = 1 L dy y, i y u y − R y i y − e vy y, i y dy dt (18) where u x and u y are the supply voltages for the xand y-axis, respectively, and R x and R y indicate the resistance of the control windings for the xand y-axis, respectively. where ux and uy are the supply voltages for the x-and y-axis, respectively, and Rx and Ry indicate the resistance of the control windings for the x-and y-axis, respectively.…”
Section: Transient Time Simulationsmentioning
confidence: 99%
“…The most accurate results are obtained for dynamic simulation models based on the finite-element method. Unfortunately, the field-circuit directly coupled FEM is very time-consuming; therefore, the second variant of this simulation model has gained popularity [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…2(a) and 2(b)) were used in order to focus the magnetic field lines in the projectile area [16]. In the case of the ICPM construction, permanent magnets as an additional source of a magnetic field (NdFeB) were implemented [17], (Figs. 2(c) and 2(d)).…”
Section: Physical Modelsmentioning
confidence: 99%
“…The iron core was used in order to focus magnetic field lines while arose from the flow of current through the electric circuit rail-projectile-rail and from the magnets in the projectile area. Previous studies had shown coincidence between measurements and calculation results for the previously made prototype of the accelerator (Waindok and Piekielny, 2017). Due to the obtained coincidence, the multivariate calculations were based on the results of the earlier worked out magnetostatic model (in Maxwell software).…”
Section: Introductionmentioning
confidence: 98%